Hippocampal adaptation to high altitude: a neuroanatomic profile of hippocampal subfields in Tibetans and acclimatized Han Chinese residents - Zhang, Lianqing; Meng, Jinli; Li, Hailong; Tang, Mengyue; Zhou, Zan; Zhou, Xingning; Feng, Li; Li, Xiangwei; Guo, Yongyue; He, Yuanyuan; He, Wanlin; Huang, Xiaoqi (Frontiers in Neuroanatomy, 2022)
The hippocampus is highly plastic and vulnerable to hypoxia. However, it is unknown whether and how it would adapt to chronic hypobaric hypoxia in human. With a unique sample of Tibetans and acclimatized Chinese Han residents at plateau, we aim to build a neuroanatomic profile of the hippocampus adapted to high-altitude by measuring their volumetric differences in the global hippocampus and their subfields. High-resolution T1 weighted magnetic resonance imaging was collected in healthy Tibetans (TH, n=72) and healthy Chinese Han residents on a high-altitude over 3500m (HH, n=27). A group of healthy Chinese Han residents in the plain (HP, n=72) was also recruited as sea-level reference. Whereas the whole hippocampal volume didn’t show a significant difference across groups when corrected with age, sex and total intracranial volume, subfield-level differences within the hippocampus were found. Post-hoc analyses revealed that the Tibetans are observed with larger core hippocampal subfields (bilateral CA3, right CA4, right dentate gyrus) and right hippocampal-amygdala transition area, and smaller ‘white matter hippocampus’ including bilateral presubiculum, right subiculum and bilateral fimbria as compared with Chinese Han subjects (HH and/or HP). HH subjects are observed with slightly but insignificant smaller hippocampus and all its subfields as compared with HP. Our data shows that while the overall hippocampal volume didn’t change, the core hippocampus in Tibetans showed an effect of adaption to chronic hypobaric hypoxia. However, this adaption may require longer than decades but generations to accumulate.